PENGEMBANGAN USAHA MINUMAN FUNGSIONAL BERBASIS PROBIOTIK (SOYGHURT) SEBAGAI PRODUK UNGGULAN DAN BERDAYA SAING - Rossi, Evy; Ayu, Dewi Fortuna; Yunita, Imelda; Diana, Ayu; Siregar, Erpiani; Yusri, Jum’atri; Zarefar, Atika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Functional drinks are growing rapidly with increasing public awareness of the importance of health and a healthy lifestyle, such as consuming functional drinks. Some of the most popular functional drinks today are probiotic drinks such as soyghurt. The objectives of this activity are 1) to socialize the importance of consuming functional drinks and provide knowledge about the benefits of functional drinks for health. 2) Diversification of Soy as a probiotic drink Soy with a variety of flavors and dishes that follow the current trend, with portable cup packaging. 3) Making the business unit of the Campus Intellectual Product Excellence Program (PUPIK) a business that meets GMP standards and has business legality so that it becomes a sustainable independent business and can enter the fung beverage industry market in Pekanbaru City. The active participation learning system method uses activity stages including preparation, procurement of raw materials, production, and marketing of functional beverage products. The results obtained are activities that have been carried out through the development of Campus Intellectual Product Enterprises (PUPIK) which are carried out by opening a Functional Food business outlet in the campus environment, participating in promotions through exhibitions and promotions through brochures and digital marketing.